Parental Self-Efficacy and Intra- and Extra-Familial Relationships - Salo Anne-Elina; Junttila Niina; Vauras Marja (SPRINGER, 2022)
Relationships are at the heart of well-being. Parental self-efficacy emerges as a powerful construct for understanding parenting and parent-child relationships. However, person-centered approaches that allow identification of different family-specific configurations of mothers' and fathers' parental self-efficacy and potential within-family discrepancies remain scarce. Families are more than the sums of their parts, and holistic approaches are needed to deepen our understanding of potential family-level accumulation of relationship well-being and vulnerability. A latent profile analysis of 249 families of preadolescents identified four family profiles of parental self-efficacy: (1) low-low, (2) low-average, (3) high-average, and (4) high-high (a mother's-a father's parental self-efficacy within the family). We further applied the Mplus auxiliary function to explore what characterizes mothers', fathers', and their preadolescents' intra- and extra-familial relationships within these profiles. Belonging to the balanced low parental self-efficacy family profile was associated with intra- and extra-familial relationship vulnerability: mothers, fathers, and preadolescents reported the highest social and emotional loneliness, parents perceived their family communication as less open, and preadolescents were evaluated as the least prosocial (in parent, teacher, and peer evaluations) and as the most antisocial (in parent evaluations). Mothers', fathers', and preadolescents' intra- and extra-familial relationship well-being was the strongest in high parental self-efficacy family profiles. Promoting parental self-efficacy can be a promising way to enhance all family members' relationship well-being. Moreover, as loneliness experiences accumulated in the balanced low parental self-efficacy family profile, efforts to tackle preadolescents' loneliness should acknowledge the well-being of all family members.